2009
DOI: 10.1007/s11121-009-0123-3
|View full text |Cite|
|
Sign up to set email alerts
|

Population-Based Prevention of Child Maltreatment: The U.S. Triple P System Population Trial

Abstract: The prevention of child maltreatment necessitates a public health approach. In the U.S. Triple P System Population Trial, 18 counties were randomly assigned to either dissemination of the Triple P—Positive Parenting Program system or to the services-as-usual control condition. Dissemination involved Triple P professional training for the existing workforce (over 600 service providers), as well as universal media and communication strategies. Large effect sizes were found for three independently derived populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
449
0
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(468 citation statements)
references
References 54 publications
9
449
0
10
Order By: Relevance
“…This program reduced the number of CM cases in a trial conducted in South Carolina. 6 Because the costs of implementing the full multilevel Triple P program have recently been published, 22 this program offers a convenient example of how our estimates can be used to demonstrate the reduction in Medicaid costs that may result from the implementation of preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This program reduced the number of CM cases in a trial conducted in South Carolina. 6 Because the costs of implementing the full multilevel Triple P program have recently been published, 22 this program offers a convenient example of how our estimates can be used to demonstrate the reduction in Medicaid costs that may result from the implementation of preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Programs have recently been evaluated and been shown to have a significant effect on preventing CM. 5,6 Whereas several prevention programs for child maltreatment have been evaluated, no study to date has developed a systematic estimate of the overall impact of CM on health care spending. A review of medical costs identified many limitations with existing studies and a wide variance in costs, from $0 to $24 000 per case of CM.…”
mentioning
confidence: 99%
“…The Triple P System is an evidence-based multilevel system program that provides parents with education, skill-building, and support to cope with the stressors of parenting and avoid child maltreatment behaviors (Sanders 1999;Sanders et al 2003;Prinz et al 2009). The Period of PURPLE Crying is another example of an evidence-based approach that teaches coping techniques to help mothers avoid abusive head trauma in response to infant crying and has been used in rural and urban communities (Barr et al 2009a,b;Schwab Reese et al 2014).…”
Section: Implications For Primary Preventionmentioning
confidence: 99%
“…Combining parenting interventions like The Triple P System (Sanders 1999;Sanders et al 2003;Prinz et al 2009) and The Period of PURPLE Crying (Barr et al 2009a,b) with elements of intimate partner aggression prevention programs may be an innovative approach to reducing family aggression. Given the unique risk associated with rural residence, translating such programs for families in rural communities must also be considered.…”
Section: Implications For Primary Preventionmentioning
confidence: 99%
“…The quality of the programs, however, is variable. The Triple P program resulted in a positive reduction of maltreatment in 1 study, 74 but the program needs to be replicated and reassessed to determine its effectiveness. 63 A comparison of the effectiveness of parent-training programs is available through the Cochrane Database of Systematic Reviews.…”
Section: Community Prevention Programs and Resourcesmentioning
confidence: 99%